Visible-light induced C3-H trifluoromethylation of quinoxalin-2(1H)-ones with CF3SO2Cl under external photocatalyst-free conditions. (16th March 2022) - Mi, Xia; Cui, Beibei; Zhang, Jingyu; Pi, Chao; Cui, Xiuling
Graphical abstract: An effective method for the synthesis of 3-trifluoromethyl quinoxalin-2(1 H )-ones was described with CF3 SO2 Cl under visible light irradiation. This reaction could be performed smoothly under photocatalyst- and oxidant-free conditions, providing an effective and green access to 3-trifluoromethyl quinoxalin-2(1 H )-ones. The methodology may be attractive for organic synthesis and pharmaceutical chemistry. Abstract: Reported herein is a visible light-induced CH trifluoromethylation of quinoxalin-2(1 H )-ones with CF3 SO2 Cl as CF3 radical source under photocatalyst-free conditions. The reaction proceeds smoothly through a radical process in the absence of photocatalyst and oxidant in moderate to good yields, thus offering an efficient and green method for the synthesis of 3-trifluoromethyl quinoxalin-2(1 H )-ones.